Inactivation in vivo of basic peroxidase and increased content of H2O2 in grapevine leaves post treatment with DTT and paraquat - Pérez, Francisco J (Journal of plant physiology, 2003)
Substantial differences in the in vivo effect of paraquat (Pq) and DTT on basic peroxidase (GBPx) activity and on H2O2 levels were found in grapevine leaves cv. Sultana. GBPx activity decreased and H2O2 levels increased in illuminated Pq treated leaf-discs. Inactivation of GBPx and accumulation of H2O2 depended on the duration and intensity of the illumination to which discs were exposed. Since GBPx was inactivated directly by H2O2 and not by Pq in leaf extracts, and since GBPx are cytosolic isoenzymes and H2O2 is a stable molecule that can easily permeate chloroplast membranes, we concluded that Pq inactivation of GBPx in vivo is mediated by H2O2. In contrast to the effect induced by Pq, DTT directly inactivated GBPx in leaf extracts. In leaf-discs, however, it reduced GBPx activity in the absence of light, although the levels of H2O2 increased only after exposure of the discs to high irradiance, suggesting that under excess of light, a significant fraction of the photosynthetically produced electrons are dissipated through the water-water cycle and H2O2 accumulates as a consequence of GBPx inactivation